The notion of motif where disciplines intersect: Folkloristics, narrativity, bioinformatics, automatic text processing and linguistics - Legallois, Dominique; Koch, Stefan Josef (Phraseology and Style in Subgenres of the Novel: A Synthesis of Corpus and Literary Perspectives, 2019)
In this chapter, we present the main elements necessary for understanding how disciplines as distinct as nineteenth-century folkloristics, narratology, bioinformatics, automatic text processing and linguistics use the term “motif.” Although their specifics differ, all are concerned with defining what is a motif, cognizing what it represents (is it a thematic or a linguistic unit?) and identifying it. With this article we therefore argue for collaboration between disciplines, which, while scientifically far removed from each other, also share a prevailing interest in tackling the question of motif.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Motif Narratology Bioinformatics Theme Automatic text processing Linguistic unit